Implementasi Metode Agile Software Development Extreme Programming Pada Sistem Informasi Pendaftaran Laboratorium - Suhadi, Ujang; Hariyanto, Dicky; Sastra, Ricki (IMTechno: Journal of Industrial Management and Technology, 2023)
Laboratory registration activities at the Hospital require good management, starting from registration, and laboratory results, this registration is still conventional where recording and reports still use paper media that is prone to tearing or loss, mistakes often occur in unexpected data storage, so from the existing problems, the author tries to design a web site portotype of laboratory registration information system design, which is used by internal circles, this design uses data collection by observation or research, interviews and literature studies, database design using Enterprise Relationship Diagrams, Logical Restructuring , as the development and design of a system with a new system can be expected to help facilitate the work of managers and the resulting information is faster, more accurate and precise in making reports, making this prototype using several software and tools such as Java, Balsamic, and MySQL.